(untitled) (Economic and Political Thought, 2013)
High unemployment rate is a problem observed not only in Poland but also in most European Union countries. Because of that, the issue of adjusting mechanisms of the labor market and methods of decreasing the unemployment rate seem to be very important, especially when the mechanisms fail. The article discusses the functioning of adjusting mechanisms in conditions of flexible and inflexible remuneration. It also analyses, on the basis of the theory and examples of contemporary economies, why the adjusting mechanisms fail on the labor market. Next, with the use of Eurostat data and simple analysis of the regression, the article presents an assessment of the labor market in Poland. Finally, the article includes conclusions on directions of addressing the unemployment problem in Poland, focusing on structural factors.